Overhauling of Kirana Stores - Sule, Abhishek; Kumar, Gourav; Poyekar, Meeta; Rajput, Rajendra; Divate, Umesh (Indian Journal of Marketing, 2009)
In India, retailing is the buzz word now-a-days. This sector has modernized and expanded at a rapid pace in sync with India's economic growth. We all can see the glorious future of retail. But the future of mom and pop stores which we know as Kirana stores looks uncertain due to the growth of modern organized retail. Experts have gone to the extent of saying that mom and pop stores will soon be extinct.